Design of digital systems and devices - Adamski, Marian; Barkalov, Alexander; Węgrzyn, Marek; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Logic design of digital devices is a very important part of the Computer Science. It deals with design and testing of logic circuits for both data-path and control unit of a digital system. Design methods depend strongly on logic elements using for implementation of logic circuits. Different programmable logic devices are wide used for implementation of logic circuits. Nowadays, we witness the rapid growth of new and new chips, but there is a strong lack of new design methods. This book includes a variety of design and test methods targeted on different digital devices. It covers methods of digital system design, the development of theoretical base for construction and designing of the PLD?based devices, application of UML for digital design. A considerable part of the book is devoted to design methods oriented on implementing control units using FPGA and CPLD chips. Such important issues as design of reliable FSMs, automatic design of concurrent logic controllers, the models and methods for creating infrastructure IP services for the SoCs are also presented. The editors of the book hope that it will be interesting and useful for experts in Computer Science and Electronics, as well as for students, who are viewed as designers of future digital devices and systems.
Part I System Design -- Part II. Digital Design With Programmable Logic -- Part III Testing, Modeling and Signal Processing.
Electronic reproduction.
Keywords: System design; Logic design; Digital electronics -- Design; Electronic books